A study of factive assertive predicates in english versus vietnamese - Trần,Thị Quỳnh Như (ĐHĐN., 2015)
This thesis examined the syntactic, semantic and pragmatic features of factive assertive predicates in English and Vietnamese. This qualitative study was based on a descriptive framework of functional grammar, speech act, epistemic modality and appraisal theory. It was carried out in a contrastive analysis with English as the source language and Vietnamese as the target one. The corpus of over 500 English samples and 500 Vietnamese ones randomly gathered from different sources such as novels, short stories and online materials …were employed to investigate the syntax, semantics and pragmatics of factive assertive predicates in expressing the speaker‘s assertion to the truth value of proposition based on funtioanl grammar, epistemic modality, and engagement framework. Syntactically, the positions, the negative addition of factive assertive predicates were mentioned. Semantic and pragmatic features were examined based on engagement resources. The most significant aspect of the study, the similarities and differences between English and Vietnamese ways of expressing speaker‘s attitude by using factive assertive predicates in the view of syntax, semantics and pragmatics, is presented in order to help learners have better use of language in communication. Besides, some suggested solutions of translation drawing from findings and discussions were expected to help Vietnamese learners of English use factive assertive predicates effectively in their communicative situations.